Highly efficient oxygen electrode catalyst derived from chitosan biomass by molten salt pyrolysis for zinc-air battery. (10th April 2020) - Qiao, Yu; Kong, Fantao; Zhang, Chaoqi; Li, Ruijing; Kong, Aiguo; Shan, Yongkui
Abstract: The highly efficient electrocatalysts with foam structure for oxygen transformation reaction were prepared by the pyrolysis of chitosan biomass in molten KCl at 800 °C and heating treatment at 800 °C (CK-800-800, where C refers to chitosan, K means molten KCl and 800 stands for temperature of pyrolysis and heat treatment). The dispersive effect and causticity of molten salt as well as isolation function of solid salt contribute to the formation of foam structure with excellent capacity of mass transmission. After heating treatment, N content, defect content and specific surface area of catalyst are raised, which results in high active site density. The obtained catalyst CK-800-800 exhibits better catalytic activity (Ehalf-wave  = 0.86 V vs. RHE), stability and methanol resistance than commercial Pt/C for oxygen reduction reaction (ORR) in alkaline media. Zinc-air battery assembled with CK-800-800 shows more excellent peak power density (178 mW cm −2 ), specific capacity (780 mAh gZn −1 ) and cycling stability than that with Pt/C. Therefore, CK-800-800 is a promising alternative to Pt/C in energy storage/conversion devices. Graphical abstract: Image 1 Highlights: Molten salt pyrolysis of chitosan biomass is adopted to prepare oxygen electrode catalyst (CK-800-800). The foam structure originates from dispersive effect and causticity of molten salt and isolation of solid salt. The optimized N species and large specific surface area raise the active site density for electrochemical reaction. The performance of Zinc-air battery assembled with CK-800-800 is superior to that with commercial Pt/C.